Training On The Use Of The Book “Balanced Nutrition Of Youth: Prevent Stunting” To Improve Adolescent Food Consumption Patterns: Pelatihan Pemanfaatan Buku “Gizi Seimbang Remaja: Cegah Stunting” Untuk Meningkatkan Pola Konsumsi Pangan Remaja - Aslis Wirda Hayati; Husnan Husnan; Roziana Roziana (STIKes Hang Tuah Pekanbaru, 2022)
The prevalence of stunting in the Southeast Asia/South-East Asia Regional (SEAR) is 36.4%. One of the efforts to prevent and reduce the prevalence of stunting is to teach teenagers about food consumption patterns based on balanced nutrition. This community service aims to improve adolescent food consumption patterns. This training is conducted from February to February. August 2022. Dietary counseling was conducted 3 times using the book